PREPARATION OF SPECIALISTS OF THE ECONOMIC FIELD IN THE HIGHER EDUCATION INSTITUTIONS OF UKRAINE AND POLAND: METHODOLOGICAL ASPECT - Zagorodnya, Alla (Continuing Professional Education: Theory and Practice, 2019)
The study reveals the essence of professional training of specialists in the economic field. The classification of documents fixing the content of professional training of specialists in the economic field (information package, structural and logical scheme for training specialists, credits, content modules, individual curricula of students, a scale for assessing student learning activities, standards, methodologies, regulations, instructions, training, thematic and work plans of teachers, methodological developments, learning programs, study complexes of disciplines, etc.) is given. The educational standard of professional training of specialists of the economic field in the Republic of Poland is analyzed on two levels, which includes an indicative list of educational disciplines, determination of the number of hours and credits required for mastering students. The list of key competencies that should master the future specialist in the economic field after two cycles of training is given. The features of the psychological and pedagogical component in the content of training of specialists in the economic field in higher educational institutions of Ukraine and Poland identified. Individual aspects of the professional activity of specialists in the economic field are determined, where it is appropriate and necessary to use knowledge in the disciplines of the psychological and pedagogical cycle. The principle of diversification in the formation of the content of professional and economic training of specialists in the Republic of Poland is disclosed. Information on the scientific principles of selection and structuring of the content of education is presented. The general and distinctive in the implementation of the content of professional training of specialists in the economic direction in higher educational institutions of Ukraine and Poland defined.